Use of re-cycled water and health hazards - Amerasinghe, Priyanie H. (2009)
Water is essential for life. World over, there is a growing demand for water resources whether it be for agriculture, industry or domestic use. Population increases adds to this burden, and with nearly half the population projected to live in cities by 2020, competition for water resources is ever increasing. Evidence is also mounting on how this precious commodity will be in short supply in the future, while climate change is influencing its distribution in the most unexpected and unpredictable manner. Given these scenarios, it is prudent and timely to re-look at conservation and re-use strategies of water. Many countries around the world are already using reclaimed water as an alternative source for a wide range of applications, including landscape and agricultural toilet and urinal flushing, industrial processing, wetland restoration and ground water recharge. However, water reclamation and re-use is not without consequences. Human health risks associated with the re-use of recycled water is one of the areas that require closer scrutiny and good planning with guidelines and regulations prior to use. This session looks at the water reuse strategies and associated health risks